PENINGKATAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK MELALUI PENERAPAN PENDEKATAN SAINTIFIK - Erwina Oktavianty; Haratua Tiur Maria Silitonga; Siti Fatimah (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2020)
This study aims to determine the effect of applying a scientific approach to improve students' critical thinking skills on static fluid material at SMA Mujahidin Pontianak. The research method used was Pre-Experimental with One Group Pre-test Post-test design. The data collection tool used was in the form of questions, namely 8 questions in multiple choice form. This study involved 25 students of class XI IPA 2 as a sample selected by random sampling technique. The results showed that the average gain score for critical thinking skills was 0.3 in the moderate category. This research is expected to be used as an alternative remediation activity for students in order to improve critical thinking skills